Genotype F Mumps Viruses Continue to Circulate in China, From 1995 to 2019 - Su, Yao; Liu, Jianyang; Liu, Mingchen; Li, Meng; Gao, Fan; Li, Changgui; Liang, Zhenglun; Wu, Xing; Mao, Qunying; Wang, Qian; Bian, Lianlian (Frontiers in Virology, 2022)
Mumps, a disease caused by the mumps virus (MuV), has been spread widely across the world, especially among children and adolescents. Recent frequent local mumps outbreaks were reported worldwide, which may be caused by the decline in the neutralization ability of the existing attenuated live mumps vaccines against circulating MuV strains which were different from the genotype A or B vaccine strains. There is an urgent need to understand the genotypes of MuV strains currently circulated globally and in China. The gene sequences of MuV strains circulated globally were collected and phylogenetic trees were constructed using different strategies. The results showed that the MuV strains previously circulated globally were predominantly genotype G, while genotype F was predominantly circulated in China, followed by genotype G. The molecular evolution of genotype F MuV strains circulated in China is at a low genetic mutation rate, and the analysis of population dynamics pattern indicates that the incidence of genotype F mumps in China showed a rebound trend. These findings provide a basis for the selection or design of vaccine strains, and the decision of the evaluation strains for immunogenicity and protective efficacy, which laid the foundation for the research and development, as well as the application of next-generation MuV vaccines.